3D porous bioadsorbents based on chitosan/alginate/cellulose nanofibers as efficient and recyclable adsorbents of anionic dye. (1st August 2021) - Mokhtari, Amir; Sabzi, Mohammad; Azimi, Hamidreza
Graphical abstract: Highlights: Novel bioadsorbents using chitosan/alginate/cellulose NFs were developed. Freeze-dried bioadsorbents demonstrated a 3D interconnected porous structure. qm of the porous bioadsorbents toward EBT dye was reached up to 2297 mg/g. Bioadsorbents preserved their stability and high adsorption capacity at various pHs. They are low-cost, green, reusable, fast, and efficient adsorbents of EBT dye. Abstract: Natural polysaccharides are attractive materials for fabrication of eco-friendly biodsorbents for efficient water remediation. However, scarcity of adsorbents that possess features of high stability and adsorption capacity at various pH conditions, low-cost, eco-friendly, and recycleability at the same time still remains a great challenge. Herein, porous ionically crosslinked biofoams were prepared by freeze-drying of chitosan (CS)/sodium alginate (SA) complex (CSA). FTIR and XRD were used to characterize the structure of the bioadsorbents. SEM observations revealed that adsorbents have a 3D interconnected porous structure, which is a favorable morphology for dye adsorption. Accordingly, CSA and its nanocomposite containing 15 wt% cellulose nanofibers (CSAC15 ) exhibited a fast and efficient adsorption behavior with qm values of 2015 and 2297 mg/g for adsorption of the Eriochrome black-T (EBT) anionic dye, respectively, which are quite outstanding among the developed EBT adsorbents in the literature so far. The CSAC15 preserved its stability and high adsorption capacity at various pH solutions. The adsorption of EBT onto the bioadsorbents was well-described with the pseudo-second order kinetics and Freundlich isotherm. The proposed CSAC15 bioadsorbent featured repeated dye removal capability after five cycles of adsorption.